Perceived ability to cope and quality of life of CAPD and hemodialysis patients - Pastor-Ugto, Claire O. (1998)
This past few decades, great attention has been given to quality of life. Science and technology has grown so rapidly that it is no longer enough to evaluate the merits of life saving procedures and machines in terms of how long they can prolong life but more importantly how do they affect the patient's life.Dialysis for instance is being prescribed to end-stage renal disease patients who can not avail of kidney transplantation. Working as a nurse in a kidney institute, one can not help but notice the different reactions of these patients to dialysis. Some view it as a second life while others looked at as an instrument of torture. These observations served as an inspiration to do a study on quality of life. Although various studies have been done on this topic, most of them describe only quality of life per se. Few dealt with the variables influencing it.This study was done to (1) describe how CAPD and hemodialysis patients cope with their health condition; (2) determine the variables relating to perceived ability to cope; (3) describe the quality of life ESRD patients according to the following domains: physical health, psychological, social relationship and environment; (4) identify the variables relating to quality of life and (5) establish a relationship between perceived ability to cope and quality of life.The study utilized a descriptive-correlational research design. Twenty CAPD and 20 hemodialysis patients who met the pre-set criteria were purposively selected. They were interviewed using the questionnaire method. Data were elicited on the following areas: personal factors, medical variables, social support, availability of human resources, adequacy of finances, perceived ability to cope and quality of life.Findings showed that the respondents perceived themselves to be coping effectively most of the time with a mean score of 11.25. To determine the variables relating to perceived ability to cope, Pearson product moment correlation Spearman's rho rank and t-test were done. Results showed that symptom score is inversely related to perceived ability to cope ( r = -.422) while availability of human resources is positively related (rho = .424). The respondents who have low symptom score and those who have somebody to care for their needs perceived themselves to be coping more effectively with their health condition.The findings also showed that these patients enjoy a fair quality of life. In fact this observation extends to all the domains. Variables relating to quality of life as a whole and those on each domain were also identified. Results showed that adequacy of finances is positively related to quality of life. The more adequate the finances of the patient is the better is the quality of life of the respondents. Adequancy of finances is also positively related to social relationship (rho = .421) and environment (rho = .349) domains of quality of life. Age (r = -.312) is inversely related to physical health domain. The younger the respondents the better is their physical health. An opposite relationship existed between availability of human resources an physical health. The more available somebody is to attend to the physical needs of the patient, the more the better is one's physical health.Finally, a positive relationship was established between perceived ability to cope and quality of life (r = .516). The respondents' perception that they are coping effectively most of the time contributed to them having a fair quality of life.Implications of these findings were made in relation to the nursing practice, nursing administration and nursing research. Recommendations were given on what avenues can be taken to help the patients cope better and live quality life.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Hemodialysis -- Patients; Quality of life; Coping